Plasma EBV DNA as a prognostic factor in EBV associated gastric cancer: a multicenter, prospective study (EBV PRESAGE study) - Alberti, Andrea; Stocker, Gertraud; Lordick, Florian; Hacker, Ulrich T.; Kobitzsch, Benjamin; Haffner, Ivonne; Baiocchi, Gian Luca; Zamparini, Manuel; Tiberio, Guido A. M.; Baronchelli, Carla; Caruso, Arnaldo; Bossi, Paolo; et al. (Frontiers in Oncology, 2023)
The Cancer Genome Atlas Research Network identified Epstein-Barr-Virus (EBV)-positive gastric cancer as a distinct molecular subtype. The prevalence is 8-9% and the histological examination shows pronounced lymphocytic infiltration, elevated levels of IFN-γ and consequently overexpression of PD-L1. The role of plasma EBV DNA load as a prognostic factor in patients with this cancer subtype is still to be defined.The present multicenter prospective observational study "EBV PRESAGE", involving German and Italian cancer centers, aims to evaluate the prognostic role of plasma EBV DNA in EBV-related gastric cancer (GC). The objective is to study the association between plasma EBV DNA load at different consecutive time points and the patient's prognosis. Every patient with a new diagnosis of gastric cancer (including gastroesophageal junction adenocarcinoma) will be screened for Epstein-Barr encoded small Region (EBER) on tissue biopsies using in situ hybridization (ISH). If EBER ISH is positive, blood analysis for plasma EBV DNA will be conducted. The plasma EBV quantitative analysis will be centralized, and extraction, detection, and quantification of EBV DNA in plasma samples will be performed using realtime PCR.We hypothesized that plasma EBV DNA represents a non-invasive tool for monitoring EBV-related GC and might be valuable as a prognostic marker.